Fatigue Cracks Detection in Rectangular Plates with Circular Hole with the Use of Elastic Waves - Barski, Marek; Stawiarski, Adam; Pająk, Piotr (Discontinuity, Nonlinearity, and Complexity, 2026)
The current work is devoted to the problem of fatigue cracks detection and evaluation in the case of isotropic rectangular plates with circular holes. The cutout is located in the geometrical center of the plate. The structure is subjected to the cyclic tension. It causes the formation of the fatigue cracks in the vicinity of the hole. This type of damages can be effectively detected by the analyzing of elastic waves propagation. In the presented work the propagation of the elastic waves in the vicinity of a hole is simulated with the use of the finite element method. It is assumed that the elastic waves are excited and picked up by piezoelectric sensors. The most effective position of the piezoelectric actuator is looked for while the position of the array of sensors is fixed. Four different possibilities of the location of the actuator are studied. Moreover, the advanced algorithm of crack detection and evaluation is also discussed.